PEMANFAATAN BIOSISTEM TANAMAN UNTUK MENURUNKAN KADAR FENOL, AMONIA, ION KLORIDA, DAN COD DARI PROSES BIODEGRADASI AIR LIMBAH YANG MENGANDUNG RHODAMIN B - Sri Dian Meita Sari; Wayan Budiarsa Suyasa; I Gede Mahardika (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
The biodegradatio nof Rhodamine B may not be directly result in CO2 and H2O, rather other pollutans such asphenol, ammonia, and chloride ions. The objective of this research are to determine the effectivity of thebiosys templants indegradating Rhodamine B and the capability to reducethe contents of phenol, ammonia, chloride ionsand COD.Concentration artificial waste Rhodamine B that used in this research are 1 mg/L. Seeding sediment using microorganism selected from dyeingwaste disposallocated in the village Pemogan, South Denpasar than disseminated into a bath biosystem in which hadgiven thesand, pebbles and Ipomeacarssicaulis. Furthermore artificial waste Rhodamine B poured into the biosystem and waste waterwere analyzed with the time rangeevery 6 hours from 0 until 48 hours.The results of the capability treatment system showed that the biosystems of plants was capable to reduce optimals levels of Phenol from 24 to 30 hours of processing amounted to 0.2906 mg / L, Ammonia from 24 to 36 hours of processing amounted to 0.1452 mg / L, Ion Klorida and COD from 18 to 30 hours of processing amounted to 2.127 mg / L and 3.848 mg / L. Biosystems plant is effective to lowering levels of phenol and ammonia (above 50%), but less effective in lowering levels of Chloride Ion and COD.